2012
DOI: 10.3748/wjg.v18.i46.6819
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion inhibits interleukin-12 and tumor necrosis factor alpha and modulates intestinal flora in rat with ulcerative colitis

Abstract: HPM treatment can regulate intestinal flora and inhibit the expression of TNF-α and IL-12 in the colon tissues of UC rats, indicating that HPM can improve colonic immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Similarly, another category of cytokines secreted from macrophages, the IL-1β, is involved in pro-inflammatory regulations that facilitates UC progression ( 48 ). In addition, T and natural killer cells are mediated by the IL-12 cytokine, which in turn fuels TNF-α secretion ( 49 ). As reported previously, pro-inflammatory cytokine levels (TNF-α, IL-12, and IL-1β) in colonic tissues were elevated significantly by DSS exposure ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another category of cytokines secreted from macrophages, the IL-1β, is involved in pro-inflammatory regulations that facilitates UC progression ( 48 ). In addition, T and natural killer cells are mediated by the IL-12 cytokine, which in turn fuels TNF-α secretion ( 49 ). As reported previously, pro-inflammatory cytokine levels (TNF-α, IL-12, and IL-1β) in colonic tissues were elevated significantly by DSS exposure ( 50 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment can reduce the expression of IL-8 and ICAM-1 mRNA and proteins in the colonic mucosa of patients with UC [ 46 ]. Previous studies have found that IL -12 and TNF- α expressions are significantly higher in UC rat colons, but herb-partitioned moxibustion reduces their expression [ 47 ]. Herb-partitioned moxibustion can also reduce the concentrations of IL-1 β , IL-6, and TNF- α from induced peripheral blood mononuclear cells (PBMCs) cultured supernatants of UC rats, relieving intestinal inflammation [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many patients, especially in China and Asia areas, try to consult traditional medical doctors to manage their conditions by acupuncture and moxibustion [ 16 ]. Up till now, reports have demonstrated that acupuncture plus moxibustion or moxibustion alone can (1) manage the symptoms of abdominal pain, diarrhea, bloody stool, and consequent weight loss [ 17 ], (2) promote recovery of damaged intestinal tissues due to inflammation [ 18 ], and (3) suppress the inflammatory response of UC [ 19 ]. However, as to the Th17/Treg, so far very few studies of acupuncture and moxibustion have direct evidence to show that they can influence the balance of these two kinds of cells.…”
Section: Introductionmentioning
confidence: 99%